If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3 = 15 + 6x Reorder the terms: 3 + 3x = 15 + 6x Solving 3 + 3x = 15 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + 3x + -6x = 15 + 6x + -6x Combine like terms: 3x + -6x = -3x 3 + -3x = 15 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -3x = 15 + 0 3 + -3x = 15 Add '-3' to each side of the equation. 3 + -3 + -3x = 15 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = 15 + -3 -3x = 15 + -3 Combine like terms: 15 + -3 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 8x-5=2x+7 | | 161+2+3x=180 | | Y=80+0.6Y+40 | | a+8(9a+4)=170 | | 3(900-n)= | | 27-6x=-9 | | 2x^2+12x+28=0 | | 1/10(a+1)=1/6(2-a) | | m/4=12 | | 3n-900= | | (8p+1)+3=-12 | | a+6(9a+4)=170 | | 8p+1+3=-12 | | (4(8x-2))/3x=10 | | 9x-6x+8=x-7+15 | | 5/4e+1/2=2e-1/2 | | N/4=15 | | 3a-8=16 | | 5xy-3x=0 | | x=5/8/10 | | -3/4N=33 | | -2/3y=16 | | (9x+2)(x^2+6x)= | | a+7(3a+-2)=96 | | .06a=-2.52 | | (4(8x-2))/3x | | 5/9+a=-4/9 | | x-(-5)=230 | | (-21-9b)+15= | | 60x[10s]= | | Y=80+0.6Y+30 | | 4(7x+6)=-60 |